Менеджмент змін в розвитку організації: підходи та моделі - Стахурська, Світлана Антонівна; Ткачук (Стахурська), Світлана Валеріївна; Стахурський, Валерій Олександрович (My University, 2020)
У статті розглядаються управлінські підходи та моделі управління організаційними змінами при управлінні змінами в розвитку організації. Визначено місце системного, динамічного, контекстного, функціонального, процесного, поведінкового, ситуаційного, адаптивного, контактного підходів при здійсненні кардинальних довгострокових, середньострокових та поточних змін. Показана універсальність низки моделей організаційних змін, а саме: триступеневої моделі Курта Левіна, восьми кроків Коттера, циклічної моделі Кемерона і Гріна, моделі К. Фрайлінгера та І. Фішера, моделі І. К. Адізеса, моделі узгодження Надлера і Тушмана, семифакторної модель Мак-Кінзі, моделі Р. Джонсона, Ф. Каста, Дж. Розенцвейга. Визнано за доцільне застосування при кардинальних довгострокових та середньострокових змінах системної моделі Сенге та моделі управління переходом Уільяма Бріджеса. Визначена раціональність використання формули змін Бекхарда і Харріса, моделі управління змінами Карнала, моделі запланованих змін Балока і Баттена, "кривої змін" Дж. Д. Дак, моделі ADKAR, моделі EASIER при поточних та середньострокових організаційних змінах. Модель Стейсі і Шоу "складні процеси як реакція на зміни" пропонується використовувати переважно для поточних змін. The article considers management approaches and models of organizational change management in change management in the development of the organization. It is noted that the need for development of the organization is determined by the variability of the environment and the need for competitive competition. These factors encourage long-term, medium-term and current organizational changes. Disturbances in the environment, depending on the amplitude of bifurcation processes, necessitate changes, in particular in changing strategies: long-term, short-term or "current". The place of system, dynamic, contextual, functional, process, behavioral, situational, adaptive, contact approaches in the implementation of cardinal long-term, medium-term and current changes is determined. The use of a systems approach is basic. When implementing long-term and medium-term organizational changes, it is advisable to give preference to the following approaches: dynamic, contextual, functional, process, behavioral. Current changes in the organization should be carried out using primarily the following approaches: situational, adaptive, process, functional, contact and behavioral. The universality of a number of models of organizational change is shown, namely: Kurt Levin's three-stage model, Cotter's eight steps, Cameron's and Green's cyclic model, K. Freilinger's and I. Fischer's model, I. K. Adizes' model, Nadler and Tushman coordination model, seven-factor model Mack -Kinsey, models of R. Johnson, F. Cast, J. Rosenzweig. Recognized as appropriate for use in the cardinal long-term and medium-term changes of the Senge system model and the transition management model of William Bridges. The rationality of using the formula of Beckhard and Harris changes, Carnal's change management model, Balok's and Batten's planned change model, JD Duck's "change curve", ADKAR model, EASIER model for current and medium-term organizational changes is determined. Stacey and Shaw's model of "complex processes as a reaction to change" is proposed to be used mainly for current changes. Any model of organizational change should not be rejected. In addition to the general sequence of actions, each of them contains a set of useful tips and warnings about possible problems in a given situation. A useful addition to the standard step-by-step and cyclical models are partial fragmentary models and practical advice on the process of implementation of changes, which some authors offer based on their own experience.
Keywords: управління; розвиток; менеджмент змін; підходи до управління; організаційні зміни; моделі управління змінами; management; development; change management; approaches to management; organizational changes; change management models; кафедра маркетингу; кафедра економіки праці та менеджменту